A randomized, double-blind, parallel-group, phase III study of shortening the dosing interval of subcutaneous tocilizumab monotherapy in patients with rheumatoid arthritis and an inadequate response to subcutaneous tocilizumab every other week: Results of the 12-week double-blind period. Issue 1 (2nd January 2018) - Ogata, Atsushi; Tanaka, Yoshiya; Ishii, Tomonori; Kaneko, Motohide; Miwa, Hiroko; Ohsawa, Shino
Abstract: Objective: To determine the efficacy and safety of subcutaneous tocilizumab (TCZ-SC) monotherapy every week (qw) versus every other week (q2w) in patients with rheumatoid arthritis who had an inadequate response to TCZ-SC q2w. Methods: Adult patients in Japan with inadequate response to TCZ-SC q2w were randomized to either TCZ-SC 162 mg qw monotherapy or TCZ-SC 162 mg q2w monotherapy for 12 weeks (double-blind). The primary endpoint was the change from baseline in adjusted Disease Activity Score 28-erythrocyte sedimentation rate (DAS28-ESR) at week 12. Efficacy, safety and pharmacokinetics were assessed. Results: TCZ-SC qw was superior to TCZ-SC q2w for adjusted mean change in DAS28-ESR from baseline to week 12. The difference in the change in DAS28-ESR between TCZ-SC qw and q2w was −1.21 (95%CI: −2.13,  −0.30, p  = .0108). A higher proportion of patients receiving TCZ-SC qw achieved DAS28-ESR remission/low disease activity than TCZ-SC q2w. Adverse events were 71.4% and 66.7% for TCZ-SC qw and q2w, respectively; infection was the most common event with one fatal case with TCZ-SC qw. Conclusions: In patients with inadequate response to TCZ-SC q2w, shortening the dosing interval to qw improved efficacy with acceptable tolerability. Occurrence of infection for both TCZ q2w and qw is important and needs careful attention.